The Influence Between Corporate Social Responsibility and Political Connections on Tax Aggressivity through Institutional Ownership As A Moderation Variable - Erianto Paembonan; Erwin Saraswati; Syaiful Iqbal (Quantitative Economics and Management Studies, 2024)
The aim of this research is to determine the influence between corporate social responsibility and political connections on tax aggressiveness through institutional ownership as a moderating variable. This type of research is quantitative research, involving all companies listed on the Indonesian Stock Exchange in the 2017-2021 year of observation as the population. The data sources used in this research are secondary data obtained from company websites and the Indonesian Stock Exchange website (www.idx.co.id). The quantity of CSR as measured by calculating how much information related to corporate social responsibility has a negative influence on the presence of tax aggressiveness within the company. CSR quality has a negative influence on tax aggressiveness, which means that CSR quality can pressure companies to be tax aggressive. The existence of political connections that a company has no effect on the tax aggressiveness carried out by the company. Institutional ownership can moderate the quantity of CSR on tax aggressiveness. Institutional ownership moderates the relationship between CSR quality and tax aggressiveness. In the analysis results, it is proven that institutional ownership strengthens the negative influence of CSR quality on tax aggressiveness. Has been proposed that institutional ownership can moderate the influence of political connections on tax aggressiveness.